Whether the use of a multidisciplinary approach may increase the adherence and effectiveness of treating patients with type 1 diabetes and type 2 diabetes? - Kohut, Anna; Frankova, Iryna; Potapov, Oleksij; Bobryk, Maryna; Komisarenko, Julia; Chaban, Oleh (Psychosomatic Medicine and General Practice, 2019)
Significance and evaluation of the impact of psychosocial factors on the treatment adherence of patients with Diabetes Mellitus type 1 and type 2 and the importance of a multidisciplinary approach to improving the efficacy of treatment.